Effective Communication among JUTH Student-Nurses and Strategies for Successful Communication: A Qualitative Study - Dajang, Innocent Nasuk; Bwai, Patricia Nathan; Yulian, Vinami (Jurnal Berita Ilmu Keperawatan, 2025)
This paper examined the place of effective communication among student nurses of Jos University Teaching Hospital (JUTH) and explored strategies to enhance their communication skills. Effective communication is crucial in nursing practice for ensuring patient safety, promoting positive outcomes, and fostering therapeutic relationships. The study was motivated by the discovery during lectures that a number of the students had challenges with basic communication. The paper randomly selected thirty participants who are Peri-Operative, Post-Basic Anesthesia, and Nephrology student-nurses from the Jos University Teaching Hospital, Plateau State, for the study and using Focus Group Discussion (FGD) as data collection method, data was elicited from the discussion and discussed in the study. The paper discovered that language barriers, cultural differences, and limited proficiency in English pose significant challenges for student nurses and widely affect their communication. The paper therefore concluded that by implementing targeted interventions such as language support programs, cultural competency training, and communication skills workshops, educators and healthcare institutions can empower student nurses to overcome language barriers and enhance their communication abilities.